Desistance or Displacement? The Changing Patterns of Offending from Adolescence to Young Adulthood - Massoglia, Michael (Journal of quantitative criminology, 2006)
Research has devoted substantial attention to patterns of offending during the transition to early adulthood. While changes in offending rates are extensively researched, considerably less attention is devoted to shifts in the type of offending displayed during the transition to adulthood. Changes in the type of offending behavior suggest a pattern of “displacement” or shifts between various types of crime, rather than desistance from deviant behavior. In this paper, I integrate methods previously developed in stratification research and use longitudinal data from the National Survey of Youth that span the transition to adulthood to examine the extent to which desistance and displacement of deviant behavior are defining attributes of offending during the transition to early adulthood. The findings indicate that while desistance is clearly present, altering patterns of offending, or within-person displacement, rather than termination of illicit activity is most evident in the data.